Monolog Kebangkitan (Tanpa Suara): Analisis Pendekatan Budaya Resepsi Sastra - Karmila br Karo; Reza Pahlevi Ginting (Journal on Education, 2023)
This study aims to analyze a drama monologue of awakening using a literary reception approach. Literary reception is a literary genre that examines literary texts by considering the reader as the giver of speech or response. This research refers to the understanding and assessment given by the audience towards the drama "Monologue of Awakening" which was carried out by taking advantage of the moment of commemoration of the Youth Pledge. The method used in this study is a qualitative descriptive method, namely describing and describing the subject or object of research that elevates the facts found in the research being studied. This Awakening Monologue tells about the attitude of Indonesian youth in responding to various issues so that Indonesia can survive, and ends with the delivery of the Youth Pledge, Language Month, and an emphasis on being proud of speaking Indonesian. From the research results, it was found that this literary reception research succeeded in getting the audience and readers immersed in the plot of the story.